Kolaborasi Karang Taruna Dalam Tata Kelola Zakat Menuju Jabar Juara - Itto Turyandi (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
This study aims to see and know the positioning and brand of BAZNAS Jabar, as a government agency that requires coordination, distribution, utilization, reporting of zakat management, infaq, shodaqoh and partnership partnerships with social organizations in West Java. The research method uses qualitative analysis with a SWOT analysis from the perspective of the management of the amil zakat body. This research resulted in a strategic planning in the short-term, medium-term and long-term planning as well as amil zakat management institutions to gain trust and acceptance and pride for the people of West Java. One of the efforts suggested is a collaborative activity with Karang Taruna West Java social organization. The conclusion shows, West Java Amil Zakat Board has more opportunities for improvement, distribution, optimization of utilization and reporting through collaboration with Youth Organization. To get human resources who like and have the capacity with capabilities as not the main in getting support, distribution, utilization, and approval of the management of zakat, infaq, shodaqoh through improving the muzaki and mustahik database with its successor, culture and wisdom of each region in West Java. The West Java Amil Zakat Agency should ideally have a tiered zakat education program to the community, to answer the challenges of the industry era 4.0 by implementing a governance regulation that is supported and optimizing the use of social media for social campaigns in zakat, infaq, shodaqoh, and social social assistance funds the other.